2018
DOI: 10.1186/s12864-018-4709-7
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of phenotypic variation and genome aberrations observed among Phytophthora ramorum isolates from diverse hosts

Abstract: BackgroundAccumulating evidence suggests that genome plasticity allows filamentous plant pathogens to adapt to changing environments. Recently, the generalist plant pathogen Phytophthora ramorum has been documented to undergo irreversible phenotypic alterations accompanied by chromosomal aberrations when infecting trunks of mature oak trees (genus Quercus). In contrast, genomes and phenotypes of the pathogen derived from the foliage of California bay (Umbellularia californica) are usually stable. We define thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 59 publications
(83 reference statements)
0
17
0
Order By: Relevance
“…While these drastic genome changes can be detrimental to the organism, formation of aneuploidy and polyploidy is an important strategy orchestrated by pathogens to adapt to the environment during periods of stress (56). Polyploidy and aneuploidy are prevalent in Phytophthora natural isolates and progeny from sexual reproduction (35, 5760). Interestingly, plant hosts can induce aneuploidy of the sudden oak death pathogen P. ramorum , which enhances its phenotypic diversity and increases its adaption to the environment (59).…”
Section: Discussionmentioning
confidence: 99%
“…While these drastic genome changes can be detrimental to the organism, formation of aneuploidy and polyploidy is an important strategy orchestrated by pathogens to adapt to the environment during periods of stress (56). Polyploidy and aneuploidy are prevalent in Phytophthora natural isolates and progeny from sexual reproduction (35, 5760). Interestingly, plant hosts can induce aneuploidy of the sudden oak death pathogen P. ramorum , which enhances its phenotypic diversity and increases its adaption to the environment (59).…”
Section: Discussionmentioning
confidence: 99%
“…While these drastic genome changes can be detrimental to the organism, formation of aneuploidy and polyploidy is an important strategy orchestrated by pathogens to adapt to the environment during periods of stress [62]. Polyploidy and aneuploidy are prevalent in Phytophthora natural isolates and in progeny from sexual reproduction [36,[63][64][65][66]. Interestingly, plant hosts can induce aneuploidy of the sudden oak death pathogen P. ramorum, which enhances its phenotypic diversity and increases its adaption to the environment [65].…”
Section: Plos Geneticsmentioning
confidence: 99%
“…In these organisms, aneuploidy has been previously reported [37,38]. Especially interesting are the reports concerning the oomycete P. ramorum, the causal agent of Sudden Oak Death [37,39]. In those reports, it was shown that the phenotype and karyotype of strains isolated from diseased trees were different than the ones grown in vitro.…”
Section: Aneuploidy and Copy-number Variations (Cnvs)mentioning
confidence: 99%